Problemy drukarstwa galicyjskiego na przełomie XIX i XX wieku w ocenie Związku Właścicieli Drukarń Galicji Zachodniej - Gruca, Anna (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
This article develops issues addressed in a letter written by Wacław Anczyc. The content of the letter presents the opinions of the Association of Owners of Printing Houses of Western Galicia and their views on the problems of Galician printing at the turn of the nineteenth and twentieth centuries. These problems include irregularities in granting licenses for running a printing house, compliance with the price list for printing works, and unfair competition in printing.